Physical Design and Mask Synthesis for Directed Self-Assembly Lithography - Shim, Seongbo (NanoScience and Technology,, 2018)
This book discusses physical design and mask synthesis of directed self-assembly lithography (DSAL). It covers the basic background of DSAL technology, physical design optimizations such as placement and redundant via insertion, and DSAL mask synthesis as well as its verification. Directed self-assembly lithography (DSAL) is a highly promising patterning solution in sub-7nm technology.